Análisis para el desarrollo de un sistema de localización en tiempo real de los historiales clínicos de los pacientes en el IESS de la ciudad de Babahoyo. - Guerrero Vargas, Ruth Vannesa (2023)
The Automation of Companies today has taken on great importance due to the facilities they offer for information management when keeping stored records and they are reflected in reports in a consolidated way, is the Case of the IESS Babahoyo Hospital , Level II, which provides medical care to the residents of the Province and its canton as well as those around it and before the great demand of patients is limited in the search for their medical records, so it is decided to carry out an Analysis to develop a real-time location system of patients' medical records in real time, which would allow a more appropriate record of information, collecting patient data to generate a report of their care and consultations, for the development of the The program will be carried out in a web compiler programming with a database, which will be hosted on a local server with backup in the cloud to guarantee that the information will always be updated and protected against any infringement, being managed solely by the health center staff. with the precautions of the case to safeguard the information of the patients of the health home.